OP0089 Genetic studies on DICKKOPF-1, sclerostin and the severity of joint destruction in rheumatoid arthritis. (23rd January 2014) - de Rooy, D.; Yeremenko, N.; Knevel, R.; Brouwer, E.; Wilson, G.; Lindqvist, E.; Saxne, T.; Krabben, A.; Leijsma, M.; Tsonaka, R.; Daha, N.; Zhernakova, S.; et al.
Abstract : Background: Inflammation in Rheumatoid Arthritis leads to impaired bone formation. The activity of the Wnt pathway influences osteoblast differentiation. Dickkopf-1 (Dkk1) and Sclerostin (Sost) are important negative regulators of bone formation, they bind and inactivate signaling of the LRP-5 receptor. This inhibition is amplified in case Dkk-1 also binds to the transmembrane receptor Kremen-1. Data are emerging that Wnt signaling is important to maintain the integrity of joints and that TNF-α induced changes in Dkk-1 affect the balance between bone formation and resorption. Objectives: Since the severity of joint destruction in Rheumatoid Arthritis is in part influenced by genetic factors, we aimed to study the influence of genetic variants in Dkk-1, Sost, LRP-5 and Kremen-1 on the radiographic progression rate. Methods: 1, 418 RA-patients with 4, 885 X-ray sets of both hands and feet of four independent cohorts were studied. First, explorative analyses were performed on 600 RA-patients enrolled in the Leiden-Early-Arthritis-Clinic on the SNPs tagging Dkk-1 (8), Sost (9), Kremen-1 (16) and LRP5 (44). Significantly associating SNPs were genotyped in cohorts from Groningen (NL), Sheffield (UK) and Lund (Sweden). In each dataset the relative increase of the progression rate per year in the presence of a genotype was assessed. Subsequently, data were summarized in a meta-analysis. In groups of 80, on their genotype selected, RA-patients from Leiden, serum levels of functional Dkk-1 and Sclerostin (Biomedica, Austria) were measured with ELISA and studied in relation to genotypes. Results: In the first cohort, 7 SNPs on Dkk-1, 3 SNPs on Sost, 1 SNP on Kremen-1 and 10 LRP-5 SNPs were significant. The SNPs on Kremen-1 and LRP-5 were not replicated in the second phase. 3 Dkk-1 SNPs associated significantly with progression of joint damage in the meta-analysis, also after FDR-correction for multiple testing (rs1896368, rs1896367 and rs1528873). Additionally, 2 Sost SNPs tended to significance (rs4792909 and rs6503475, p=0.01 and 0.03 in the meta-analysis and p=0.07 after FDR-correction). Epistasis between SNPs on Dkk-1 and Sost was observed. Sclerostin levels were not correlated to the SNPs in Sost . However, serum levels of Dkk-1 were significantly correlated with the genotypes in rs1896368 and rs1896367 (p=0.002). Patients carrying risk alleles (associated with more radiographic progression) had higher levels of Dkk-1. Conclusions: The present data of four cohort studies show that RA-patients carrying the risk alleles of several genetic variants in Dkk-1 have higher serum levels of functional Dkk-1 and more progressive joint destruction over time. These data illustrate the relevance of Dkk-1 to progression of joint destruction in RA. Disclosure of Interest: None Declared